Serious games to support emotional regulation strategies in educational intervention programs. Systematic review and meta-analysis - Gómez León, Maria Isabel (Heliyon, 2025)
In recent years, there has been an increase in emotional and behavioral disorders in children and adolescents that directly affect their personal, school, family, and social spheres. It has been proposed that serious games designed to train emotional regulation skills can be a more effective, accessible, and attractive alternative for children and adolescents than conventional therapies. However, there is a limited number of studies providing evidence of the effectiveness of these applications. The aim of this review is to analyze the level of effectiveness, feasibility and acceptability of serious games designed to train emotional regulation skills in children and dolescents aged 6 to 18 classified in universal population samples, at risk and diagnosed. A systematic review of papers published between 2008 and 2023 was conducted following the PRISMA statement guidelines. The databases Scopus, Web of Science, PubMed, ERIC, IEEE Xplore, and ACM Digital Library were used. Thirty-three articles were identified that referred to 18 serious games designed to train emotional regulation skills in children and adolescents. All studies used report or self-report measures to code for the recognition of emotions in oneself and the increase or decrease of these emotions. Internal validity was assessed using the Cochrane RoB 2 tool for randomized controlled trials and the ROBINS-I tool for non-randomized studies. A random effects model was implemented, and the effect sizes were calculated as Hedge’s g. Although there are limitations in interpreting the results, such as the lack of long-term follow-up, serious game interventions that incorporated biofeedback provided the strongest evidence for generalizability of learned emotion regulation skills to real life. While this does not always imply a clinically significant change, the results show that serious games can be effective, acceptable, and feasible for learning emotional regulation strategies and reducing symptoms related to depression, anxiety, and lack of impulse control.
Keywords: Serious games; Applications in subject areas; Teaching/learning strategies; Improving classroom teaching; Special needs education; Emotional